Predicting Negotiation Performance from Personality Traits: A field Study across Multiple Occupations. Issue 3 (27th May 2018) - Sharma, Sudeep; Elfenbein, Hillary Anger; Foster, Jeff; Bottom, William P.
ABSTRACT: Based on decades-old reviews, many negotiation researchers have expressed doubts about the effect of personality on negotiation outcomes. More recent reviews have found significant associations between traits and outcome measures. Existing research has primarily used laboratory experiments; field studies are rare. In this study, we aim to fill that important gap. Traits measured using the Hogan Personality Inventory were correlated with supervisor ratings of negotiation performance across three occupations: marketing managers, lawyers, and construction supervisors. Ambition and likability independently predicted greater negotiation performance. Results generalized across these three samples with evidence for an interaction effect in the lawyer sample. For attorneys, greater ambition was not additionally helpful for those who were relatively more likable. Results establish the importance of negotiation effectiveness as a distinct component of overall job performance. Practical implications are considered in terms of division of labor, person–job fit, and the state-trait distinction.